Retrieval of weather information for climate change monitoring using ground-based GPS network - Yahya, Mohd. Hafiz; Kamaruddin, Md. Nor (2008)
Global Positioning System (GPS) is a multi-satellites positioning system that consists of 24 satellites, arranged in nearly circular orbital planes at an altitude of about 22,000 km above the earth surface. Denoted as an efficient satellite-based positioning tool yet available, GPS provides real time three-dimensional positioning, velocity information and time in common reference system 24 hours a day. In spite of its appreciable applications in navigation, surveying and mapping, petrology, open-pit mining, precision farming and earth deformation study, there has been a resurgence of interest among European countries and other developed nations towards the use of GPS as an effective yet practical tool for meteorological applications. Taking the advantage of existing GPS tracking networks worldwide, this paper highlights the retrieval of the least understood weather information namely precipitable water vapour (PWV) for climate change monitoring. Given that appropriate strategies are employed during data acquisition and data processing, it is noted that there are lots of advantages using ground-based GPS network for the purpose of retrieving the highly variable PWV. It is suggested that through the aspect of accuracy and practicality, ground-based GPS network is sufficiently adequate to satisfy the demands of in-depth understanding on the spatial and temporal variability of weather information, contributing to the aftermath of climate changes.